Exploring the Services of the Incubation Centres on the Performance of Start-Ups in Kerala - Shameera, M.K.; Vennila, D. (Indian Journal of Information Sources and Services, 2025)
Incubation centres have a significant role in promoting innovation, entrepreneurship development and thereby economic growth in a country. They are the main catalysts to attain the per capita income of an industrialized nation. This study analyses the effectiveness of the services of incubation centres on the performance of Start-ups in Kerala. The variables for measuring the service effectiveness were identified from the literature. A structured questionnaire was used to collect primary data from 313 Start-ups. A proportionate sampling method was adopted in the study. Correlation and multiple regression analysis were used to analyse the data. The result derived from correlation indicate that all the variables of the service effectiveness of Incubation Centre’s such as Incubation Services, Mentorship Programmes, Business Counselling and Advice, Legal Services, Marketing Support, Co-working Space or desk Cabin Space, Funding Support or Services and Internet based services have significant association with the Performance of Start - ups and regression analysis reveals that there is a positive effect of the variables of Service Effectiveness of Incubation Centres on the Performance of Start-ups. This study is important to policymakers and governments, as it guides the foundation for building structured policies and programmes that generate employment opportunities, growth in the economy, and innovation.